Development of the Shafi'iyyah Fiqh Thought Pattern and the Role of al-NawawÄ« as a Unifier - Imran, Helmi; Lawang, Karimuddin Abdullah (Institut Agama Islam Negeri Curup, 2022)
This study aims to find factors for the emergence and development of the ShafiÃ School of legal thought and the role of al-NawawÄ« as a unifier of these thoughts. Legal thought in the ShafiÃ school of thought at the beginning of the revival of the school was very diverse, so this also affected the legal analogy that developed between one region and another. This research is a qualitative research, in which the data were analyzed by using content analysis based on the text of the thoughts of the scholars. Based on the results of the study, it can be understood that the birth of various styles of thought in the ShafiÃ school was caused by the different methods of thinking of the scholars from different regions in developing the ShafiÃ school of thought, such as the areas of Iraq and Khurasan. Iraqi scholars prefer the riwÄyah method while Khurasan scholars prefer the dirÄyah method. In addition, each of these styles of thinking has advantages and disadvantages. The advantage of the Iraqi style is in the transmission of mazhab opinions and the rules of ijtihad, so that this style of thinking is considered stronger than Khurasan, while the Khurasan style lies in the systematic method of legal development, so that this style is considered better in legal development cases. The weakness of the Iraqi style of thought is in terms of takhrÄ«j and tafrÄ«â€™ compared to the Khurasan style, while the Khurasan style is weak in terms of the accuracy of the transmission of opinions compared to the Iraqi style. This has inspired the scholars who lived afterward, such as al-NawawÄ« (d. 676 H) to initiate the unification of these styles of thought. Therefore, al-NawawÄ« is seen as the most representative of the Shafi'iyyah scholars in developing the Shafi'i school.